Anti-CD20 therapies in pregnancy and breast feeding: a review and ABN guidelines. Issue 1 (8th July 2022) - Dobson, Ruth; Rog, David; Ovadia, Caroline; Murray, Katy; Hughes, Stella; Ford, Helen L; Pearson, Owen R; White, Sarah; Bonham, Nicola; Mathews, Joela; Nelson-Piercy, Catherine; Brex, Peter
Abstract : Neurologists increasingly use anti-CD20 therapies, including for women of childbearing age, despite these medications being unlicensed for use in pregnancy. Current evidence suggests that women can safely conceive while taking anti-CD20 therapy. Women should not be denied treatment during pregnancy when it is clinically indicated, although they should be counselled regarding live vaccinations for their infant. Women receiving regular ocrelizumab for multiple sclerosis should preferably wait 3 months before trying to conceive. There are few data around ofatumumab in pregnancy, and while there is probably a class effect across all anti-CD20 therapies, ofatumumab may need to be continued during pregnancy to maintain efficacy. We recommend that anti-CD20 therapies can be safely given while breast feeding. It is important to make time to discuss treatments with women of childbearing age to help them choose their most suitable treatment. Outcomes should be monitored in pregnancy registries.